2004
DOI: 10.1016/j.nuclcard.2004.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

Potential utility of rubidium 82 PET quantification in patients with 3-vessel coronary artery disease

Abstract: Quantification of Rb-82 net retention to measure the stress-rest perfusion difference in the myocardium defined a greater extent of disease than the standard approach in this group of patients with triple-vessel disease. More accurate measurement of the extent of coronary artery disease could facilitate better risk stratification and identify more high-risk patients in whom aggressive intervention is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
175
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(178 citation statements)
references
References 33 publications
1
175
0
2
Order By: Relevance
“…[85][86][87] • In general, hyperemic MBF and MFR are relatively preserved for coronary lesions with less than 70% angiographic stenosis or with preserved fractional flow reserve (FFR) ([ 0.8). 45,47,51,52,[85][86][87][88][89]91,141,142 However, both Figure 7. Receiver-operator characteristic curves for detection of severe CAD using MFR.…”
Section: Reporting Quantitative Mbf Datamentioning
confidence: 94%
See 3 more Smart Citations
“…[85][86][87] • In general, hyperemic MBF and MFR are relatively preserved for coronary lesions with less than 70% angiographic stenosis or with preserved fractional flow reserve (FFR) ([ 0.8). 45,47,51,52,[85][86][87][88][89]91,141,142 However, both Figure 7. Receiver-operator characteristic curves for detection of severe CAD using MFR.…”
Section: Reporting Quantitative Mbf Datamentioning
confidence: 94%
“…Stress-first or stress-only imaging is feasible, but it is not routine practice with quantitative PET. Although several studies have suggested that peak hyperemic MBF is superior to MFR, [45][46][47] most studies have concluded that MFR is more powerful for risk stratification, [48][49][50][51][52][53] perhaps because of decreased variability compared with peak hyperemic MBF. 54 Whether postischemic stunning affects resting MBF with stressfirst imaging has not been well studied.…”
Section: Imaging Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of MBF and coronary-flow reserve provides information on both the macro-and the micro-circulation and likely more accurate detection of both early and advanced disease [5][6][7]. Do these technical advantages and improved accuracy justify the use of PET in clinical routine?…”
mentioning
confidence: 99%